Egeria najas Planchon (Hydrocharitaceae) responses to abiotic short-term environmental changes - Pezzato, Maura Maria; da Cunha-Santino, Marcela Bianchessi; Camargo, Antonio Fernando Monteiro [UNESP]; Bianchini, Irineu (Springer Nature, 2024)
Understanding the factors that control the growth of macrophytes is of paramount importance in predicting their distribution and management. This study describes the effect of short-term variation of pH, light intensity (10–390 µmol m−2 s−1), and temperature (15–30 °C) over the gross photosynthetic rate, respiration rate and net photosynthetic rate (NP) of Egeria najas in nutrient limited condition, and high nutrient availability. The light and dark bottles method was utilized to measure photosynthesis. The pH increase from 4.0 to 8.5 promoted a continuous decrease in NP. Temperature had an important effect on the NP value, with variations in Q10 from 1.42 to 2.23. Although maximum NP rates occurred under low light intensity (158–204 µmol m−2 s−1), in short-term, the availability of light can represent the main factor controlling photosynthesis in rooted E. najas; nevertheless, dissolved nutrients can highly induce the growth of free-float specimens. Our results facilitate the understanding of E. najas potential to colonize since it easily adapts to changes in environmental conditions.
Keywords: Light intensity; Narrow-leaf elodea; Net photosynthetic rate; Nutrients availability; pH; Temperature